Read, Write, and Navigation Awareness in Realistic Multi-view Collaborations - Junuzovic, Sasa; Dewan, Prasun; Rui, Yong (CollaborateCom 2007, 2007)
Read, write, and navigation awareness allow users of a multi-view collaborative editor to get fine-grained information about whether others are reading what they are editing, where others are editing, and to which areas of the document others have navigated, respectively. We derive new high-level tools that directly support the three kinds of awareness. The results of a decision-making study involving the use of these tools revealed that write awareness helps with fine-grained conflict prevention, read awareness reduces unnecessary verbal communication, and navigation awareness is most effective when coupled with read and write awareness. Thus, the study identifies specific uses of the three forms of awareness and motivates tools for supporting them.